Food waste in bakeries- quantities, causes and treatment - Iakovlieva, Maryna (2021)
Bread waste represents a considerable part of food waste in Sweden, and in general, food waste can have a significant impact on the environment. This study assesses the quantity of food waste in bakeries and identifies the main causes of waste during the production of baked products. A sample was taken from the total number of bakeries in Sweden. In this study, 19 bakeries were analysed. Information for the analysis was obtained through telephone interviews and digital video calls with employees or bakery managers. For three bakeries, the study was also complemented by interviews conducted through face-to-face meetings. Based on the collected data, this study concluded that bread losses in small bakeries accounted for about 1.5% of total production, and up to 20% of losses in large bakeries, including bread returned from supermarkets. The following reasons were identified as the seven main causes for the loss of bread and bakery products: technical difficulties, equipment failure, equipment repair, incorrect sizes of bread and bakery products during production (shape, low weight), expiration date, incorrect order and return of bread due to low demand. One major cause of the loss of bakery products was also the human factor. All used resources invested in the production of bakery products that are not sold such as water, fertilizers, land and energy, used in the production, transport and storage of food products are also lost. Improvements to production processes in bakeries are of great importance, which can affect or reduce the amount of bread and bakery products not sold. It is likely that bakeries can adjust orders and forecasts for the amount of bread and baked products produced to minimize the proportion of losses.